Migrasi Orang Jawa ke Asahan pada Masa Kolonial - Bayu Wicaksono (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article aims to reconstruct the history of Javanese migration to Asahan during the Dutch colonial period. The migration of Javanese to Asahan was the impact of the labor demand in the massive plantation industry sector on the East Coast of Sumatra. This study uses historical research methods using primary and secondary sources. The rapid development of plantations in Asahan made entrepreneurs bring in Javanese to sustain the company. To fulfill the needs of Javanese coolies, an agency was formed that has a special task of bringing in workers from Java Island. The life of the coolies is built with various facilities such as hospitals, cleanliness, housing, public kitchens, schools, and many others. Plantation entrepreneurs issue special monetary policies that aim to narrow the space for coolies by printing “kebon money” which only applies to plantations. The Javanese who migrated to Asahan were not able to achieve the hope of living a more decent life than their hometowns in their hometowns, they were instead caught in the trap of capitalists whose labor was exploited as coolies in remote areas of the plantation.